THE CONCEPT OF ‘THINGS’AND THEIR DEFINITION IN THE NEW CZECH CIVIL CODE FROM THE PERSPECTIVE OF ROMAN LAW - Michal Skřejpek (Zeszyty Prawnicze)
KONCEPCJA RZECZY I ICH DEFINICJA W NOWYM CZESKIM KODEKSIE CYWILNYM Z PERSPEKTYWY PRAWA RZYMSKIEGO